Assessment of Total Mercury Levels in Clarias gariepinus from the Sagua la Grande River, Cuba - De La Rosa D; Lima L; Olivares-Rieumont S; Graham DW; Enriquez I; Diaz O; Bastías JM; Muñoz O (Bulletin of Environmental Contamination and Toxicology, 2008)
Total mercury levels (Thg) were quantified in Clarias gariepinus captured from the Sagua la Grande River (Cuba) in the vicinity of an active chlor-alkali plant, and relationships among place of capture; fish size, weight, and sex; and THg levels were assessed. THg levels ranged from 67 to 375 ng/g ww in collected fish, never exceeding the Cuban recommended maximum limit for fish consumption of 500 ng/g ww. No significant correlation was observed between mercury levels and fish allometric characteristics (p